Fenway Park Modernization - Foundations For A Red Sox Nation - Mark H. Balfe (Deep Foundations Institute, 2011)
Over the last decade, Fenway Park has undergone annual improvements to modernize the facility for players and fans. These renovations include the Monster Seats, the Right Field Roof expansion, a new pavilion behind home plate, expansion of the Red Sox clubhouse, additional roof seating, and concourse improvements. Retrofitting the historic ballpark to bring it up to current standards required installation of foundations to support the new structural loads for each of the alteration projects. This required evaluation of existing conditions, and in many cases augmentation of the foundations at existing columns to accommodate the structural changes to the park. New foundations, generally consisting of drilled-in micropiles, were installed in numerous configurations and conditions. Since 2003, a total of 215 drilled-in micropiles have been installed to augment various columns around the park. The micropiles range in capacity between 40 and 70 tons and are installed through Fill and Organic Soils and embedded into the dense Glaciofluvial Sand and Gravel layer. Issues and learning related to the foundation augmentation include schedule constraints (work is typically conducted during the off-season and schedule is very aggressive), encountering old/abandoned utilities or foundations, ventilation of equipment, and management of spoils during micropile installation.